Upaya Mempertahankan Bersihan Jalan Napas Pada Anak dengan ISPA - Rahmawati, Laily; , Siti Arifah, S.Kp., M.Kes; , Irdawati, S.Kep.,Ns.,M.Si.,Med (2017)
Background: Acute Respiratory Infections are one of the most common causes of death in children in developing countries. Acute respiratory infection is caused four of the 15 million estimate of deaths in children under 5 years old each year, as many as two-thirds of these deaths are babies. The incidence by age group Toddlers estimated 0.29 episodes per child / year in developing countries and 0.05 episodes per child / year in developed countries. Episode cold in Toddlers in Indonesia is estimated to 2-3 times/year. The problem that usually occurs is ineffective airway clearance. Airway clearance is important because the airway is the main road to the air circulation in the body so that the cell metabolism is necessary to sustain adequate respiratory function. If the airway clearance is not maintained then the patient will experience airway obstruction resulting in ineffective airway clearance Objective: provide a real experience to the author in the management efforts should be made to provide nursing care to maintain airway clearance in pediatric patients with respiratory tract infections I. Methods: The method used is a case study approach in ARD patients in health centers and home Polokarto patient. , The manner in which the author is through the collection of primary data and secondary data. The primary data obtained from direct observation of patients, interviews with patients and families, physical examination while the secondary data obtained by looking at medical records, and is supported by journals and books related to the theme of ISPA. Results: The patients showed patency / looseness airway, had not felt clogged nose, coughing is reduced after a given action. The influence of inhaled user to maintain airway clearance. Conclusion: airway clearance issue is resolved. nursing actions semifowler positioned to maximize ventilation, steam inhalation, the manufacture of traditional medicine for ISPA in the form of lime and soy sauce awarded after the intervention affect the cleanliness of the airway. Recommended for patients and their families to perform actions such as steam inhalation of nursing independently and producing traditional medicines ISPA in the form of lime and soy sauce.